Autochthonous Lactic Acid Bacteria Isolated From Dairy Cow Feces Exhibiting Promising Probiotic Properties and in vitro Antibacterial Activity Against Foodborne Pathogens in Cattle - Lin, Wen-Chin; Ptak, Christopher P.; Chang, Chi-Yu; Ian, Man-Kei; Chia, Min-Yuan; Chen, Ter-Hsin; Kuo, Chih-Jung (Frontiers in Veterinary Science, 2020)
Bovine enteric bacterial pathogens are a major cause of health decline in agricultural cattle populations. The identification of host-derived microbiota with probiotic characteristics is key for the development of treatments utilizing pathogen displacement and recolonization by commensal flora. In this study, intestinal microbiota in fecal samples from four Holstein dairy cows were analyzed using 16S ribosomal RNA gene next generation sequencing (NGS), leading to the identification of three Lactobacillus isolates (L. gasseri, L. reuteri and L. salivarius). By taking advantage of the preferential growth in acidified culture media, bacterial characteristics examination, and restriction fragment length polymorphism (RFLP) analysis of 16S rRNA genes, the three lactic acid bacteria (LAB) strains were successfully isolated. The three LAB isolates possess the prerequisite growth tolerances for probiotic functionality as well as exhibit effective antimicrobial potency against enteric bacterial pathogens of cattle, including E. coli O157:H7, Salmonella spp. (S. Enteritidis, S. Typhimurium, and S. Dublin), and Mycobacterium avium subspecies paratuberculosis (MAP). Moreover, the LAB isolates showed significant adhesion to cattle intestine, implying greater survivability potential due to their species specificity when administered in the same host species. The isolates were susceptible to most antibiotics with the exception of streptomycin resistance in L. gasseri and kanamycin resistance in L. salivarius. Genes attributed to specific antibiotic resistances demonstrated a low risk of lateral transfer in a conjugation study. Our in vitro results demonstrate the promising probiotic characteristics of these newly identified Lactobacillus strains and their considerable potential to serve as probiotics feed supplements for cows.